Microorganism identification and environmental cleaning effectiveness in radiology settings: cross-sectional and experimental studies - Ding, Sandrine; Weber, Nicolas; Oppliger, Anne (Radiography Open, 2020)
Introduction: Despite the large number of patients passing through and some invasive procedures, radiology may still be considered unlikely to transmit pathogens. However, radiation protection aprons touched by radiology professionals and shared between patients could be prone to contamination. Our goals were to (1) assess qualitatively and quantitatively the microorganisms present on the radiation protection aprons with a cross-sectional study, and (2) determine the effectiveness of routine cleaning with an experimental design. Methods: For objective 1, 108 samples were collected on radiation protection aprons of two radiology settings: the diagnostic radiology (DR) setting, with a cleaning procedure in place, and the emergency setting without. Total cultivable bacteria, staphylococci, enterobacteria and fungi were quantified. For purpose 2, the number of total bacteria and staphylococci were compared between before and after cleaning the aprons. Results: The median number of total bacteria were respectively 0.97 and 1.56 cfu/cm2 in the DR and emergency settings, whereas the median number of Staphylococcus were 0.04 and 0.15 cfu/cm2 in these settings (Objective 1). Thus the number of microorganisms were lower in the setting with the cleaning procedure, although significantly only for staphylococci (p = 0.025). Enterobacteria, fungi and Staphylococcus aureus were not detected in any sample. In the second part of the study, the median number of total bacteria dropped from 0.80 to 0.17 cfu/cm2 between before and after cleaning (p = 0.0017) and for Staphylococcus it decreased from 0.84 to 0.15 cfu/cm2 (p = 0.13). Conclusion: A number of microorganisms have been found, although the absence of enterobacteria, fungi and S. aureus is reassuring as they can cause serious healthcare-associated infections. Our study showed that the cleaning of radiation protection aprons can significantly reduce the microbial load and should be encouraged.